Pengembangan Bahan Ajar Berbasis Aplikasi Kvisoft Flipbook Menggunakan Model Pembelajaran Problem Based Learning dengan Pendekatan Saintifik - Damayanti, Annisa; Nursalam, (Alauddin Journal of Mathematics Education, 2022)
The purpose of this study was to determine the process of developing Kvisoft Flipbook Application-Based Teaching Materials Using a Problem Based Learning Model with a Scientific Approach for class X SMAN 3 Makassar which is valid, practical, and effective. The type of research carried out is research and development (Research And Development) which refers to the ADDIE development model which consists of 5 stages, including: Analysis, Design, Development, Implementation, and Evaluation. Kvisoft Flipbook Application-Based Teaching Materials Using a Problem Based Learning Learning Model with a Scientific Approach was developed with the help of the Kvisoft Flipbook application. The subjects of this study were students of class X SMAN 3 Makassar. The instruments used in this study were validation sheets, learning implementation observation sheets, teacher response questionnaires and student response questionnaires, observation sheets on teacher's ability to manage learning, student activity sheets, and learning outcomes tests. Based on the results of the validation obtained an average of 3.81 (very valid). Practically, the average learning implementation observation sheet is 1.68 with the complete implementation category, the teacher response questionnaire analysis is 89,72% in the very positive category and the student response questionnaire analysis is 88.58% in the very positive category. Effectively, with the average percentage of the teacher's ability to manage learning in the observation sheet is 4,375, the average percentage of student activity sheets is 81%, and the percentage of students' learning completeness is 80%. So it can be concluded that the application and development of Kvisoft Flipbook Application-Based Teaching Materials Using a Problem Based Learning Model with a Scientific Approach for class X SMAN 3 Makassar has met the valid, practical, and effective categories.